517 Understanding Distinctions in the Implementation of Learning Health System (LHS). (April 2022) - Easterling, Doug; Perry, Anna; Gesell, Sabina
Abstract : OBJECTIVES/GOALS: The LHS concept has been promoted as a means for health systems to improve quality, safety, efficiency and equity. NAMs definition has been widely adopted, but is broad and has led to variation in how LHS is operationalized. Drawing on a taxonomy developed through a review of literature, we developed a tool that shows how LHSs are implemented in practice. METHODS/STUDY POPULATION: The LHS Implementation Assessment Tool (LHS-IAT) will indicate which forms of work are being carried out by a health system that purports to operate a LHS. LHS-IAT is based on the LHS Consolidated Framework (LHS-CF); which was developed through a qualitative analysis of LHS literature. LHS-CF contains 38 primary elements' and 56 secondary elements' that have been associated with the LHS construct. These elements are organized into 5 bodies of work (e.g.; translating evidence into practice) and 4 enabling conditions (e.g.; supportive culture). LHS-IAT assesses whether a health system operating as an LHS is implementing each of the key elements in LHS-CF. The usefulness of LHS-IAT will be demonstrated by applying the tool to 5 LHSs that have been described in the literature. RESULTS/ANTICIPATED RESULTS: LHS-IAT produces a quantitative profile for any given health system operating as a LHS; each LHS element is assessed as either emphasized; otherwise present; or absent. With this information, we create profiles for each implementation of LHS, using spider graphs. Systems that emphasize different elements will have different shapes for their spider graphs. Based on our initial coding of publications, we expect at least 4 distinct profiles within our sample, reflecting differences in emphasis on factors such as: continuous improvement practices, adoption of internally and externally tested interventions, research conducted to address patient care issues prioritized by institutional leaders, investigator-initiated research, clinician-engaged research, and engagement of patients and families. DISCUSSION/SIGNIFICANCE: The LHS-IAT will show differences in how health systems are translating the LHS concept into practice. This will allow for a shared language for those studying and/or implementing LHS. With the ability to map out an approach, health system leaders will have a tool to clarify intent and gain consensus as to which LHS model they want to implement and invest in.